Mechanism Insight into enhanced photodegradation of pharmaceuticals and personal care products in natural water matrix over crystalline graphitic carbon nitrides. (1st August 2020) - Wang, Yingfei; Jing, Binghua; Wang, Fengliang; Wang, Suicao; Liu, Xun; Ao, Zhimin; Li, Chuanhao
Abstract: Pharmaceuticals and personal care products (PPCPs), an emerging class of highly recalcitrant water contaminants, have raised considerable concerns in environment community. Graphitic carbon nitride (CN) has shown a great potential towards the photodegradation of water contaminants under visible light irradiation. However, the conventional bulk CN (BCN) presents the amorphous structure, resulting in an inefficient yield of hydroxyl radicals (OH) for the complete mineralization of PPCPs. This study provides fundamental insights into significantly enhancing the hydroxyl radical generation via improving the crystallinity of the pristine CN materials. Experimental measurements and accompanying density functional theory (DFT) computational analysis suggest that the crystalline carbon nitride (CCN) exhibited an enhanced adsorption ability towards the dissolved O2. Upon the light irradiation, the adsorbed O2 molecules readily undergo a direct two-electron reduction reaction on the CCN surface, instead of the conventional two successive single-electron reduction reactions on the BCN surface, to produce H2 O2 subsequently converting into OH radicals. Along with the improved charge separation efficiency and electron transfer ability, CCN-based materials show superior photocatalytic activity towards PPCPs-type pollutants, compared with the pristine BCN catalysts. Importantly, the catalyst show excellent photodegradation activities under natural sunlight irradiation, at low PPCPs concentration (20 μg/L), in the mixed PPCPs solution or in the real wastewater/water samples, indicating the potential of CCN to enable practical ex situ destructive treatment of PPCPs-contaminated groundwater. Graphical abstract: Image 1 Highlights: Crystalline carbon nitrides (CCN) exhibited enhanced photocatalytic activity. Pharmaceuticals and personal care products (PPCPs) were readily degraded by CCN. Photocatalytic degradation of PPCPs in natural water matrix was enabled by CCN. CCN presents a higher yield of H2 O2 subsequently converting into hydroxyl radicals.